Improving the fabrication uniformity of ZnO nanowire UV sensor by step-corner growth mode. Issue 11 (1st August 2018) - Gao, Zhiyuan; Zhang, Jie; Li, Jiangjiang; Xue, Xiaowei; Zhao, Lihuan; Lu, Liwei; Deng, Jun; Wan, Peiyuan; Cui, Bifeng; Zou, Deshu
Abstract: Uniformity in mass-fabrication of nanostructured device is important for its practical application. In this paper, we developed a step-corner growth mode to on-chip fabricate uniform oblique-bridged ZnO nanowire UV sensor. By strictly controlling the microelectronic processing including photolithography and magnetron sputtering procedures during the seed layer deposition and electrode fabrication, ZnO NW array could nucleate at the upper step-corner of the seed layer due to the high catalytic activities at the surface steps and kinks, and then grow in a distribution of circular sector to form an oblique bridging configuration, which guaranteed the device performance and uniformity at the same time. For the within-chip uniformity, in a 4 × 4 sensor array that randomly chosen under the 365 nm UV light of 2.5 mW/cm 2 and at the bias voltage of 1 V, the light-to-dark current ratio all kept in the level of 10 6 with the average value of 1.84 × 10 6 . There were 75% of them in the range of 1.1 × 10 6 ~ 3 × 10 6 . The detectivity all kept in the level of 10 15 Jones with the average value of 3.53 × 10 15 Jones. There were 75% of them in the range of 2 × 10 15 ~4 × 10 15 Jones. For the chip-to-chip uniformity, in 12 packaged devices that randomly chosen from three fabrication lots, the light-to-dark current ratio all kept in the level of 10 6 with the average value of 2.70 × 10 6 . There were 75% of them in the range of 1 × 10 6 ~ 3 × 10 6 . The detectivity all kept in the level of 10 15 Jones with average value of 3.69 × 10 15 Jones. There were 75% of them in the range of 1 × 10 15 ~ 4 × 10 15 Jones. The uniformity would deteriorate if the step height of seed layer was short, because NW would nucleate at the lower corner of the step and difficult to form the oblique bridge. Fabrication uniformity was also influenced by the step exposure degree, the compactness of the seed layer and the flatness of the substrate.